2022
DOI: 10.1039/d2cy01040b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient methanol steam reforming over ZnCeZrOx: the unique role of cerium

Abstract: Metal oxide catalysts have been widely used in steam reforming of methanol (SRM), but facing the challenge of long-term running. Herein, we report a ZnCeZrOx catalyst that can operate in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…29−31 Recently, our group found that ZnZrO x solid solutions rich in Ov is capable of dissociating H 2 O at temperatures above 200 °C. 32 Our and other's work suggest that (mixed) metal oxides catalyze SRM mainly through the HCOOH pathway. 32−34 Based on previous results, it is reasonable to presume that enhancing the decomposition activity of formate species and migration rate of H species may be one of the efficient approaches to increase the low-temperature SRM activity of (mixed) metal oxides.…”
Section: ■ Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…29−31 Recently, our group found that ZnZrO x solid solutions rich in Ov is capable of dissociating H 2 O at temperatures above 200 °C. 32 Our and other's work suggest that (mixed) metal oxides catalyze SRM mainly through the HCOOH pathway. 32−34 Based on previous results, it is reasonable to presume that enhancing the decomposition activity of formate species and migration rate of H species may be one of the efficient approaches to increase the low-temperature SRM activity of (mixed) metal oxides.…”
Section: ■ Introductionmentioning
confidence: 53%
“…Previous studies suggest that mixed metal oxides with solid solution structure rich in oxygen vacancies (Ov) are favorable for H 2 O dissociation and Ov is the main site for H 2 O dissociation. Recently, our group found that ZnZrO x solid solutions rich in Ov is capable of dissociating H 2 O at temperatures above 200 °C . Our and other’s work suggest that (mixed) metal oxides catalyze SRM mainly through the HCOOH pathway. Based on previous results, it is reasonable to presume that enhancing the decomposition activity of formate species and migration rate of H species may be one of the efficient approaches to increase the low-temperature SRM activity of (mixed) metal oxides. Compared to (mixed) metal oxides, supported metal catalysts are more efficient in the decomposition of intermediate formate species and in the migration of H species …”
Section: Introductionmentioning
confidence: 76%
“…Compared with ZrO 2 (20.9%), introducing Zn induced the formation of oxygen vacancies as the surface O V concentration increased to 23.4% . This number was further increased to 27.1% following the introduction of Ce, which was due to the presence of Ce 3+ . , …”
Section: Results and Discussionmentioning
confidence: 99%
“…38 This number was further increased to 27.1% following the introduction of Ce, which was due to the presence of Ce 3+ . 39,40 The relative concentration of the O V was further analyzed by capturing unpaired electrons in EPR measurements, and the results are shown in Figure 3b. The signal at g = 2.003 corresponded to electrons trapped on O V .…”
Section: Identification Of the Active Sites For The Inhibition Of Cok...mentioning
confidence: 99%
“…HCOOH is produced from the reaction of HCHO with OH species and decomposes into CO 2 and H 2 subsequently. In the later work, the promotion effect of Ce on ZnZrO x was studied by Li et al 234 Characterization results from XRD and Raman show that Zn and Ce incorporate in the lattice of t -ZrO 2 , forming ternary solid solutions in the composition range studied. Zn 1 Ce 0.5 Zr 9 O x appears to be more active than the Zn 1 Zr 10 O x and Zn 1 Ce 10 O x , achieving methanol conversion of 99.8% at 400 °C.…”
Section: Methanolmentioning
confidence: 98%